The Influence of Asmaul Husna Dhikr on Adolescent Emotional Intelligence - Evi Ni’matuzzakiyah (International Journal of Social Science and Religion (IJSSR), 2020)
Today, the reality of the condition of Indonesian society shows that there are symptoms of deterioration caused by a shift in the noble values ​​of the nation. Rampant juvenile delinquency and violation of norms, emotional intelligence is a basic condition for using intellectual intelligence effectively. Asmaul Husna's reading habit is one of the character education being pursued by the Surya Global Yogyakarta College of Health Sciences. Students are also trained and educated to develop their skills and mentality in a positive direction so that these educational institutions can produce superior and Islamic output, which is not only rely on theory in learning, but also experience in the field in facing the flow of globalization. The gap between the theory and practice of Asmaul's reading habits Husna with the level of students 'emotional intelligence, it is necessary to revisit considering the effect of Asmaul Husna's reading habit on students' emotional intelligence is not known. The research design is quantitative using the Emotional Intelligence Scale. The research was conducted at the College of Public Health Sciences. The research subjects were 65 adolescents, they were asked to fill in the pretest before Asmaul Husna dhikr intervention was carried out, and after going through the dhikr process for ten weeks the research subjects were asked to fill in the posttest. Pretest and posttest data were analyzed through the Wilcoxon test using SPSS 16. Based on the above results, it is known that the significance of 0.031 is smaller than 0.05, so it can be concluded that "Ha is accepted" This means that there is a difference in emotional intelligence between before and after Asmaul Husna's dhikr, so it can also be concluded that "There is an influence of Asmaul Husna's dhikr on adolescent emotional intelligence.